SAS and Elite Forces guide manhunt the art and science of tracking high profile enemy targets/c Alexander Stilwell ; illustrations, Julian Baker - Stilwell, Alexander (Lyons Press, 2012)
From searching for high-value enemy targets such as Osama bin Laden and Saddam Hussein to finding soldiers caught behind enemy lines, from escaped prisoners and serial killers to a missing child, Manhunt explores just how the military and police forces track people down. Including many case studies of high-value targets, suspected criminals and fugitives from justice, and with extensive background on the different techniques in tracking used, from traditional Native American trackers' skills to the latest high-tech methods, Manhunt brings together the history and science of tracking. Illustrated with 350 maps, photographs and drawings, The SAS and Elite Forces Guide to Manhunts: Tracking High Value Enemy Targets is an authoritative examination of tracking from footprints to forensics and a must for anyone interested in the latest military practices and survival skills.